AYAT-AYAT TAUHID TERHADAP BUDAYA PEMELIHARAAN KERIS DI JAWA (STUDI KASUS BUKU MT ARIFIN) - Sayyida Sayyida (Qur'an and Hadith Academic Society, 2017)
This paper discusses the tawheed verses on the culture of keris maintenance in Java. The Javanese, considering the kris as a result of the process of creation, taste, intention, and work. Keris is a special weapon of the Javanese tribe and also as a weapon of ancestral relics to be preserved. Ancient keris function is as a weapon used to puncture at close range. The existence of kris, other than as a piercer weapon as well as a high value of artwork. So there is a change of perception in a keris is certainly there and become a separate phenomenon for the community. MT Arifin is a Javanese society of Islam from the Muhammadiyah group who believe the existence of a keris. He often saw his grandfather meram (bathing) the keris in suro month (Muharram), from where the beginning of his knowledge of the kris. MT Arifin is a Muslim from Muhammadiyah group who understands keris and expert in the science of pemberisan, besides he is also a political and military observer. Muhammadiyah is a group that strongly opposes the existence of tahayyul, bid'ah, and khurafat. The results showed that the keris is a typical weapon of the Javanese as evidenced by several temples on the island of Java. The temples on the island of Java some of them found an embossed image that describes the existence of a keris-shaped weapon. The function of the current keris is as a collection of objects that contain the meaning of pasemon (story). The benefits of a kris according to the Islamic view are as a means of protecting themselves from threats.